The Influence of Internal and External Factors on Labor Productivity: A Study on the Construction Project of the Manokwari Substations - Sandryawal; Silitonga, Roland Y. H. (The Indonesian Institute of Science and Technology Research, 2025)
The construction of the Manokwari Substation in West Papua, part of Indonesia’s national strategic infrastructure program, faces geographic, logistical, and human resource challenges that demand high labor productivity to ensure project success. This study aims to analyze the influence of internal and external factors on labor productivity within this construction context. Employing a quantitative approach with a correlational ex post facto design, data were collected through a census-based closed-ended Likert-scale questionnaire distributed to 50 active workers involved in the project. Multiple linear regression analysis was used to assess both simultaneous and partial effects of the independent variables on labor productivity. The results indicate that internal factors, such as work experience, education level, health status, and wages, significantly affect productivity, while age and the number of dependents show no meaningful impact. Conversely, all examined external factors (field conditions, weather, and the implementation of occupational safety and health) significantly contribute to labor productivity. This study offers a substantial theoretical contribution by reinforcing the conceptual framework of labor productivity in the construction sector. It provides practical implications in the form of evidence-based strategies to improve workforce performance. The findings are expected to serve as a basis for policy decisions in managing strategic infrastructure projects, particularly in geographically complex regions like Eastern Indonesia.